IMPLEMENTASI METODE ICE BREAKING DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA - Basit, Abdul; Rosidi, Ahmad (International Conference on Humanity Education and Society (ICHES), 2024)
The aim of this research is to describe the implementation of the ice breaking method in increasing student learning motivation in the Islamic Cultural History subject at MA Ar-Rohmah Suren. This research uses a qualitative research approach. The results of this research indicate that the ice breaking method has been implemented at the MA Ar-Rohmah institution. At this institution the ice breaking method is implemented by several teachers. Teachers who implement the ice breaking method adapt to student needs or the situation in the classroom. Even though the implementation does not correspond to the stages of ice breaking, the purpose of implementing ice breaking has been felt by the students. When studying, students feel very motivated because there is a different atmosphere in the class or the learning time is more cheerful and enthusiastic. Students don't feel bored in class because there are breaks in boring learning, so that in the end students get excellent grades.